2010
DOI: 10.1088/2041-8205/723/1/l1
|View full text |Cite
|
Sign up to set email alerts
|

Record-Setting Cosmic-Ray Intensities in 2009 and 2010

Abstract: We report measurements of record-setting intensities of cosmic-ray nuclei from C to Fe, made with the Cosmic Ray Isotope Spectrometer carried on the Advanced Composition Explorer in orbit about the inner Sun-Earth Lagrangian point. In the energy interval from ∼70 to ∼450 MeV nucleon −1 , near the peak in the near-Earth cosmic-ray spectrum, the measured intensities of major species from C to Fe were each 20%-26% greater in late 2009 than in the 1997-1998 minimum and previous solar minima of the space age (1957-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
153
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(161 citation statements)
references
References 45 publications
(61 reference statements)
7
153
1
Order By: Relevance
“…Mason et al (2009) found that during the recent Minimum 23/24 in comparison with the previous one (22/23) there were many more co-rotating interaction regions observed, connected with the existence of more high-speed streams of solar wind. Moreover, a low solar-wind dynamic pressure, ≈ 40 % in comparison with the previous minimum, was observed (Mewaldt et al, 2010) and this was caused by the drop in the average proton density, which was ≈ 5.5 cm −3 , being less dense in comparison with the previous three minima by ≈ 70 % (Jian, Russell, and Luhmann, 2011). All of the phenomena and processes mentioned caused diminishing of the solar-modulation influence on GCR intensity and its variations.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Mason et al (2009) found that during the recent Minimum 23/24 in comparison with the previous one (22/23) there were many more co-rotating interaction regions observed, connected with the existence of more high-speed streams of solar wind. Moreover, a low solar-wind dynamic pressure, ≈ 40 % in comparison with the previous minimum, was observed (Mewaldt et al, 2010) and this was caused by the drop in the average proton density, which was ≈ 5.5 cm −3 , being less dense in comparison with the previous three minima by ≈ 70 % (Jian, Russell, and Luhmann, 2011). All of the phenomena and processes mentioned caused diminishing of the solar-modulation influence on GCR intensity and its variations.…”
Section: Introductionmentioning
confidence: 81%
“…All of the phenomena and processes mentioned caused diminishing of the solar-modulation influence on GCR intensity and its variations. McComas et al (2008) recognized a shrinkage of the size of the heliosphere (caused by the drop of the solar-wind dynamic pressure), which should result in an increase in the GCR intensity at 1 AU (Mewaldt et al, 2010). Indeed, the GCR intensity values measured by neutron monitors were the highest ever recorded (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations of B at 1 au (http://cdaweb.gsfc.nasa.gov/) show that B reached the minimum value of 4 nT in mid-2009. This minimum was associated with a historically low minimum of solar activity (McDonald et al 2010;Mewaldt et al 2010;Ahluwalia & Ygbuhay 2011;Ahluwalia & Jackiewicz 2012;McComas et al 2013). Solar activity during solar cycle 23 decreased to minimum value in August 2009, when the monthly mean sunspot number was zero.…”
Section: Introductionmentioning
confidence: 99%
“…Cosmic rays (CRs) 7,8 at Lagrangian point L2 are essentially composed by massive particles: about 89% of protons, 10% of alpha particles, 1% are the nuclei of heavier elements and less than 1% of electrons like beta particles. The total flux of CRs peaks around 200 MeV, giving a total proton flux of 3000 -4000 particles m −2 sr −1 s −1 GeV −1 .…”
Section: Introductionmentioning
confidence: 99%